Natural Convection and Thermal Stratification in a Biomass Oven Fueled by Non-Carbonized Kesambi Leaf Briquettes: An Experimental Study - Jemmy Jonson Sula Dethan; Fredrik Julius Haba Bunga; Erich Umbu Kondi Maliwemu (The University of Lampung, 2026)
This study investigates the vertical temperature distribution, natural convection behavior, and thermal performance of a biomass oven fueled by non-carbonized Kesambi leaf briquettes. Temperature measurements were conducted at multiple vertical positions inside the oven to characterize heat distribution and buoyancy-driven airflow during operation. The results show a clear vertical temperature stratification, indicating that heat transfer within the oven is dominated by natural convection without external airflow assistance. Dimensionless analysis revealed Rayleigh numbers on the order of 10⁸–10⁹, confirming the prevalence of buoyancy-induced convection, while the Nusselt number varied dynamically in response to changes in temperature difference and operating conditions. The middle region of the oven (50–60 cm from the base) consistently exhibited the most stable thermal conditions, identifying it as the most effective zone for heat utilization and smoking applications. The thermal efficiency of the oven ranged from 32% to 38%, with variations primarily influenced by combustion intensity and transient heat losses through uninsulated walls and the chimney. These findings demonstrate that non-carbonized Kesambi leaf briquettes can provide stable heat output for biomass ovens and offer practical insights for optimizing oven height, heating zones, and design improvements in small-scale food processing applications.